Identification of miRNAs involved in fruit ripening in Cavendish bananas by deep sequencing. (December 2015) - Bi, Fangcheng; Meng, Xiangchun; Ma, Chao; Yi, Ganjun
Abstract Background MicroRNAs (miRNAs) are a family of non-coding small RNAs that play an important regulatory role in various biological processes. Previous studies have reported that miRNAs are closely related to the ripening process in model plants. However, the miRNAs that are closely involved in the banana fruit ripening process remain unknown. Methods Here, we investigated the miRNA populations from banana fruits in response to ethylene or 1-MCP treatment using a deep sequencing approach and bioinformatics analysis combined with quantitative RT-PCR validation. Results A total of 125 known miRNAs and 26 novel miRNAs were identified from three libraries. MiRNA profiling of bananas in response to ethylene treatment compared with 1-MCP treatment showed differential expression of 82 miRNAs. Furthermore, the differentially expressed miRNAs were predicted to target a total of 815 target genes. Interestingly, some targets were annotated as transcription factors and other functional proteins closely involved in the development and the ripening process in other plant species. Analysis by qRT-PCR validated the contrasting expression patterns between several miRNAs and their target genes. Conclusions The miRNAome of the banana fruit in response to ethylene or 1-MCP treatment were identified by high-throughput sequencing. A total of 82 differentially expressed miRNAs were found to be closely associated with the ripening process. The miRNA target genes encode transcription factors and other functional proteins, including SPL, APETALA2, EIN3, E3 ubiquitin ligase, β-galactosidase, and β-glucosidase. These findings provide valuable information for further functional research of the miRNAs involved in banana fruit ripening.